Influence of Surface-Modification via PEGylation or Chitosanization of Lipidic Nanocarriers on In Vivo Pharmacokinetic/Pharmacodynamic Profiles of Apixaban - Mohamed F. Zaky; Taha M. Hammady; Shadeed Gad; Abdullah Alattar; Reem Alshaman; Ann Hegazy; Sawsan A. Zaitone; Mamdouh Mostafa Ghorab; Mohamed A. Megahed (Pharmaceutics, 2023)
Nanostructured lipid carriers (NLCs) have been proven to significantly improve the bioavailability and efficacy of many drugs; however, they still have many limitations. These limitations could hinder their potential for enhancing the bioavailability of poorly water-soluble drugs and, therefore, require further amendments. From this perspective, we have investigated how the chitosanization and PEGylation of NLCs affected their ability to function as a delivery system for apixaban (APX). These surface modifications could enhance the ability of NLCs to improve the bioavailability and pharmacodynamic activity of the loaded drug. In vitro and in vivo studies were carried out to examine APX-loaded NLCs, chitosan-modified NLCs, and PEGylated NLCs. The three nanoarchitectures displayed a Higuchi-diffusion release pattern in vitro, in addition to having their vesicular outline proven via electron microscopy. PEGylated and chitosanized NLCs retained good stability over 3 months, versus the nonPEGylated and nonchitosanized NLCs. Interestingly, APX-loaded chitosan-modified NLCs displayed better stability than the APX-loaded PEGylated NLCs, in terms of mean vesicle size after 90 days. On the other hand, the absorption profile of APX (AUC0-inf) in rats pretreated with APX-loaded PEGylated NLCs (108.59 µg·mL−1·h−1) was significantly higher than the AUC0-inf of APX in rats pretreated with APX-loaded chitosan-modified NLCs (93.397 µg·mL−1·h−1), and both were also significantly higher than AUC0-inf of APX-Loaded NLCs (55.435 µg·mL−1·h−1). Chitosan-coated NLCs enhanced APX anticoagulant activity with increased prothrombin time and activated partial thromboplastin time by 1.6- and 1.55-folds, respectively, compared to unmodified NLCs, and by 1.23- and 1.37-folds, respectively, compared to PEGylated NLCs. The PEGylation and chitosanization of NLCs enhanced the bioavailability and anticoagulant activity of APX over the nonmodified NLCs; this highlighted the importance of both approaches.